PENGARUH PERKEMBANGAN PASAR MODERN BERSKALA PELAYANAN REGIONAL DI KAWASAN PERKOTAAN KUDUS TERHADAP PERUBAHAN PENGGUNAAN LAHAN DI SEKITARNYA (STUDI KASUS : PASAR MODERN KUDUS EXTENSION MALL) - Dyah Ayu Lupitasari; Winny Astuti; Galing Yudana (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2016)
The development of modern market especially regional modern market is growing rapidly. The regional modern market is not only growing in urban areas but up to a small town like Kudus City. Regional modern market which is growing in Kudus City is Kudus Extension Mall. This modern market is the first and largest modern market in the Kudus City. The modern market is able to serve the region at the regional scale consisting of Kudus Regency society and also surrounding districts like Demak, Jepara, Pati to Rembang. In 2011 Kudus Extension Mall was growing rapidly indicated by the expansion and changes the name from Plasa Kudus to Kudus Extension Mall. The modern market developments affecting the condition of land use in its surrounding area. Based on these issues, the formulation of the problem in this research is how the influence brought by the development of modern markets Kudus Extension Mall in affecting land use changes in its surrounding areas. The aim of this research is to determine the influence of the Kudus Extension Mall developments to changes in land use in its surrounding areas. The method used to determine the level of influence the development of the Kudus Extension Mall to changes in land use in the surrounding areas is quantitative descriptive. These results indicate that the development of Kudus Extension Mall able to encourage changes in land use that has similar activities that are commercial and supporting activities such as residential and public service facilities. The emergence of these activities leads to changes in land use in the form of extensive changes in land use functions and intensity of land use.